Study Of Information Seeking Pattern On The People Who Receive Social Assistance In West Java - Kismiyati El Karimah, Kismiyati El Karimah; Agus Setiaman, Agus Setiaman (2015)
The title of this study is the Study of Information Seeking Pattern on The People Who Receive Social Assistance in West Java, "The site chosen for this study is Sukabumi precisely Jampang Central District, the decision to chose Jampang Central as a location for research is based on the consideration that this area is an area with the vulnerability of social caused by high social assistance, as well as the selection on Cibeber District of Cianjur Regency. The key to development success is the people's participation. This means there are perspective that had to be changed. The people should be seen not as on objects of development but rather as actors of development itself. The awareness of the existence of the people as central actors in determining the development strategy and in its manifestations is important. The inclusion of the people in national development have long been touted both by the New Order government as well as during current reign, but the implementation of these policies at this stage of the operation in the field seems to have various obstacles. This shows political awareness is not enough and that the political will is far more important, not just at the policy level but at the level of implementation.